Aniridia with lenticular and choroidal coloboma. Issue 2 (March 2021) - Angmo, Dewang; Dewan, Lubhavani; Behera, Aswini; Gagrani, Meghal
This case report presents a rare association of a complete aniridia with lenticular and choroidal coloboma. An 8-year-old female patient was referred to our glaucoma clinic with aniridia, nystagmus and bilateral corneal opacity with right eye being phthisical. Ultrasonography of the phthisical eye revealed the presence of an old closed funnel retinal detachment. Further examination under anaesthesia revealed lens coloboma in the inferonasal quadrant and presence of a choroidal coloboma in the left eye. The intraocular pressure was 28 mmHg with a central corneal thickness of 693 µm. A macula sparing laser barrage around the colobomatous area was done in the left eye and topical ocular hypotensives were started.